The detection of a synthetic Interleukin‐1 receptor antagonist peptide in a seized product from a racing stable. Issue 9 (11th September 2015) - Levina, Vita; Timms, Mark; Vine, John; Steel, Rohan
Abstract : A synthetic Interleukin‐1 receptor antagonist peptide with the sequence Acetyl‐Phe‐Glu‐Trp‐Thr‐Pro‐Gly‐Tyr‐Trp‐Gln‐Pro‐Tyr‐Ala‐Leu‐Pro‐Leu‐OH has been identified in a vial seized during a stable inspection. The use of peptide‐based Interleukin‐1 receptor antagonists as anti‐inflammatory agents has not been previously reported, making this peptide the first in a new class of sports doping peptides. The peptide has been characterized by high‐resolution mass spectrometry and a detection method developed based on solid‐phase extraction and liquid chromatography ‐ triple quadrupole mass spectrometry. Using in vitro and in vivo models to study the properties of the peptide after administration, the peptide was shown to be highly unstable in plasma and was not detected in urine after administration in a rat. The poor stability of the peptide makes detection challenging but also suggests that it has limited effectiveness as an anti‐inflammatory drug. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A novel sports doping peptide with anti‐inflammatory properties is characterised after detection during a stable inspection.